Трансфер технологій і формування інноваційної стратегії в промисловій галузі української економіки - Жуков, С. А. (Видавництво Львівської політехніки, 2015)
Визначено значення трансферу технологій для реалізації інноваційних процесів у промисловості України. Встановлено важливість державної підтримки та регулювання трансферу технологій. Обґрунтовано, що перспективним товаром на світових ринках є і буде високотехнологічна промислова продукція. Проаналізовано проблеми побудови ефективної національної інноваційної системи України. На основі оцінювання стратегій інерційно-ринкової та інноваційного прориву, запропоновано механізм реалізації іннова- ційної стратегії у промисловій галузі України. Perspective direction of world trade is a high-tech industrial product. Among the Ukrainian industrial production is the production of competitive high-tech industry. For such products primarily relates Production of military-industrial complex and dual-use products. To develop these products, it is necessary to build an effective national innovation system in Ukraine. Part of the innovation system should be a system of technology transfer. The object of this article is to study economics and innovative processes that accompany it. Technology transfer is the direction of forming innovative type of economy, it is a tool for innovative development of enterprises, industries and countries. Technology transfer contributes to the modernization and expansion of production, new products and additional revenue. Unlike other countries, in Ukraine this process is still at infancy and requires detailed study. Thus, the problem in the communication technology is a new phenomenon in various fields of Ukraine and is relevant area of research. In addition, an important element in building innovative type of economy is to develop innovative strategies in the industrial sector. The article summarizes the importance of technology transfer to industry of Ukraine and the role of government support and regulation system of the process. Proved, that the prospects for the development of domestic military-industrial complex should be considered in unity with the development of dual-use technologies. Established that there are two versions mechanism for implementing the strategy for socio-economic and technological development of innovation and Ukraine – is inertia-market strategy and the strategy of innovative breakthrough. Advantages and disadvantages of the main provisions of each of these strategies have been evaluated by the author. The consequence of inertial-market strategy will be low economic growth and the degradation of the economic structure, curtailment of research and innovation potential. To implement this strategy by using the prediction that formed the government program. However, the forecast for the practice does not provide the acceleration in economic growth; innovation and modernization of fixed assets increase the competitiveness of industrial products. Advantages strategy of innovative breakthrough is obvious and the author is given preference implement the strategy of innovative breakthrough in the industrial sector of Ukraine. This is a mechanism to improve the functioning of the national innovation system. Based on the research done by the following conclusions: 1) given the poor state of fixed assets industry Ukraine, improving innovation processes is only possible revitalization on the creation and transfer (transfer) technology at both the company and at the industry and the country; 2) in Ukraine technology transfer and innovation in high-tech industry is controlled by the state; 3) Production of military-industrial complex and dual-use products is and will be the basis for constructing an effective national innovation system in Ukraine, which will be based on a system of technology transfer; 4) The strategy of innovative breakthrough is a promising way out of the industrial sector of Ukraine crisis and building on its base of innovative modern competitive economy in the world. Thus, the basis of the innovation system in Ukraine is technology transfer and innovative breakthrough strategy. This suggests the need for further research in this direction. Yes, need additional study of the issue of resource support system technology transfer strategy of innovative breakthrough, the formation of the national innovation system as in the industrial sector of Ukraine, and in the economic system as a whole.
Keywords: трансфер технологій; високотехнологічна продукція; інноваційна стратегія; військово-промисловий комплекс; продукцію подвійного призначення; промислова галузь; technology transfer; high-tech products; innovation strategy; the militaryindustrial complex; dual-use products; industrial sector